Seeding food security: Overcoming barriers to quality potato seed adoption among smallholders in Kenya - Margaret N. Mwangi; Wilckyster N. Nyarindo; Marther W. Ngigi; Hezron N. Isaboke (PLoS ONE, 2026)
Access to quality seed potatoes is essential for boosting productivity and food security among smallholder farmers. However, the adoption and use of these seeds remain low in Kenya, thus constraining yield potential and dietary diversity. This study investigates the adoption, level of use, and impact of quality seeds on household food security among smallholder farmers in Kenya. Using a semi-structured questionnaire, data were collected from 541 households through a multi-stage sampling approach. The Heckman two-stage model estimated factors influencing adoption and usage intensity, while the propensity scores matching model assessed the impact of quality seed use on household food security. The findings indicate that about 44% of farmers used quality seeds, with significant barriers including unavailability, limited accessibility, and high cost of these seeds. Key drivers of adoption and usage intensity included the level of education, total land size, household income, access to extension, digital information, credit access, membership in a farmers’ organization, access to subsidies, livestock portfolio, and geographical location. Adopting quality seeds enhanced household food security, as evidenced by significantly higher household dietary diversity scores (HDDS) and food consumption scores (FCS). This improvement was largely attributed to increased intake of nutrient-dense foods, particularly animal-source proteins, fruits, and vegetables. These results underscore the need for policies that enhance local certified seed multiplication and distribution to increase access and reduce the cost of quality seeds. Supporting the adoption of quality seeds can substantially improve agricultural productivity and strengthen food and nutritional security.